2015
DOI: 10.1177/1057567715610631
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Known Criminals on the Proportion and Seriousness of Intimate Partner Violence Incidents

Abstract: This study examines a hypothesis that has not received adequate scrutiny: that an important proportion of intimate partner violence (IPV) incidents, particularly those that are more serious, involve generalist offenders known to the police. Many criminological theories and empirical studies suggest that offenders are often generalists, yet few IPV studies consider this hypothesis. Based on a sample of 52,149 IPV incidents recorded by police, we found that 31% of IPV incidents involved suspects only with crimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
(105 reference statements)
0
3
0
3
Order By: Relevance
“…À chaque mois qui passe, peu importe le contexte de la violence, les caractéristiques de la victime, du conjoint violent ou de la relation, les probabilités que la violence physique s'intensifie augmentent. Cette aggravation à travers le temps a déjà été confirmée à l'aide de données policières (Bland et Ariel, 2015 ;Ouellet et al, 2016) ainsi que par des études qualitatives qui se sont basées sur la dynamique des violences en contexte conjugal (Winstock, 2008). Nos résultats incitent donc à une intervention rapide avant que la violence ne dégénère.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…À chaque mois qui passe, peu importe le contexte de la violence, les caractéristiques de la victime, du conjoint violent ou de la relation, les probabilités que la violence physique s'intensifie augmentent. Cette aggravation à travers le temps a déjà été confirmée à l'aide de données policières (Bland et Ariel, 2015 ;Ouellet et al, 2016) ainsi que par des études qualitatives qui se sont basées sur la dynamique des violences en contexte conjugal (Winstock, 2008). Nos résultats incitent donc à une intervention rapide avant que la violence ne dégénère.…”
Section: Discussionunclassified
“…De leur côté, les études orientées vers l'agresseur tendent à conclure qu'il existe certains points communs entre les auteurs de violence conjugale. Les hommes plus âgés (Hayes, 2015) et les personnes qui présentent une consommation d'alcool abusive (Devries et al, 2013 ;Ouellet et Cousineau, 2014 ;Piquero, Theobald et Farrington, 2014), qui possèdent des antécédents criminels (Ouellet et al, 2017 ;Ouellet et Cousineau, 2014 ;Ouellet, Paré, Boivin et Leclerc, 2016 ;Piquero et al, 2006) et qui présentent une personnalité antisociale (Theobald, Farrington, Coid et Piquero, 2016 ;Theobald, Farrington, Ttofi et Crago, 2017), sont davantage à risque d'être auteurs de violence conjugale. Kingsnorth (2006) présente une étude sur la récidive des auteurs de violence conjugale dans laquelle il analyse simultanément des caractéristiques sociodémographiques et judiciaires de l'agresseur.…”
Section: Les Facteurs De Risqueunclassified
“…These studies suggest that it is possible to predict the parameters of IPV and to identify the various factors associated with changes. Ouellet et al (2016) attempted to predict changes in the severity of IPV incidents that involved current or former partners and had been reported to the police in a large metropolitan city in Canada (N = 53,429 incidents) between 2000 and 2009. Their results show that each new incident involving the same aggressor or victim increases the likelihood that future incidents of IPV will be more serious.…”
Section: Dynamics Of Intimate Partner Violencementioning
confidence: 99%
“…As the presence of children can modulate the level of violence their presence or absence was considered, with 68% of women reporting one or more child living with them. Recent studies have shown the impact of criminal history on the severity of IPV (Ouellet et al, 2016(Ouellet et al, , 2017, with victims of IPV with criminal records 17% more likely to be involved in more serious incidents of violence (Ouellet et al, 2016). A total of 29% of the women interviewed reported having a criminal record.…”
Section: Static Factorsmentioning
confidence: 99%
“…Ce résultat appuie la perspective féministe en montrant que les risques de répétition des violences sont plus prononcés lorsque le premier incident enregistré par les policiers implique une victime de sexe féminin et un agresseur de sexe masculin. En fait, ce résultat nuance et complète un constat obtenu dans une étude précédente avec les mêmes données (Ouellet, Paré, Boivin et Leclerc, 2016), qui montre que bien que les évènements de ce même cas de figure sont moins graves (pris de manière isolée). Nos résultats permettent toutefois d'ajouter qu'il est plus probable que les incidents dont la victime est une femme et l'agresseur un homme se répètent, un effet aggravant des nouvelles victimisations ayant été démontré dans la recherche précédente.…”
Section: Résultatsunclassified